A study to determine adverse event following immunization using COVISHIELD vaccine for prevention of COVID-19 infection in a field practice area of urban health center - Sarika P Patil; Sushant S Chavan; Amol D Kinge; Vikrant S Pagar (Asian Journal of Medical Sciences, 2022)
Background: The COVID-19 vaccination program was introduced in India on 16 January 2021. The Government-issued fact sheet was the only source of information regarding Adverse Events Following Immunizations (AEFIs) for these vaccines. Aims and Objectives: The objective of this study was to assess the AEFI reported following COVISHIELD vaccination in an urban health center. Materials and Methods: The spontaneous reporting method was used for data collection for 3 months. A data collection form was designed to collect the data from the study population who reported adverse events. Collected data were analyzed and categorized by severity and seriousness. The causality assessment was done using the World Health Organization’s causality assessment algorithm. Results: A total of 3,486 doses of COVISHIELD vaccine were administered at the study site during the study period. In all, 306 AEFIs were reported from 190 subjects with an incidence rate of 5.45%. The majority of the subjects with AEFIs belonged to the age group of 18–45 years. Out of the total 306 AEFIs, 287 AEFIs were expected as per the fact sheets. Most of the AEFIs (59.47% [n=182]) were observed at the system organ class of “General disorders and administration site conditions.” After the causality assessment, out of 433 AEFIs to COVISHIELD vaccine, 94.22% (n=287) of events were categorized to have “consistent causal association with immunization.” All of them recovered from their adverse events without any sequelae. Conclusion: Most common AEFI after COVISHIELD vaccination was found to be general disorders and administration site conditions. No severe AEFI reported.